ПОЭЗИЯДА ИНСАНЫЙЛЫҚҚА НӘЗЕР (Г.НУРЛЕПЕСОВА ДӨРЕТИЎШИЛИГИ МЫСАЛЫНДА) - Оразбаева, Г.У. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the content of the poems about human qualities and their importance in human life. On the basis of the examples the author emphasizes the educational importance of the poetry of G.Nurlepesova for the young generation.
Keywords: poetry; themes; humanity; friendship and truth in the poems; creation